(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2021)
Fourteen black cumin genotypes were evaluated against standard checks for two consecutive years during 2018 to 2019 at Sinana, Goro and Gindhir to investigate high yielder and stable black cumin varieties. The mean total seed yield of genotypes across environment ranged from 24.54 to 16.07 Qt ha-1. The highest total seed yield was recorded from genotypes 242826-2 followed by 242826-2 (24.54 and 23.32 Qt ha-1) while the lowest total seed yield was obtained from local checks. These two genotypes have yield advantage of 22.41 and 14.96% over standard check Derbera. Based on their performance across location over standard checks these two genotypes will be promoted for variety verification for Bale mid altitude and similar agro ecologies. Int. J. Agril. Res. Innov. Tech. 10(2): 35-37, December 2020